Menelusuri Jejak dan Rupa ‘Spesies Selebritis’ - Gustaman, Budi (Masyarakat Sejarawan Indonesia, 2020)
This study attempts to describe the visualization of Komodo dragons based on the records of expedition, scientific journals, newspapers, and magazines in the period 1912-1939. The Komodo dragon has been so popular since P.A. Ouwens first published a scientific journal about Komodo dragons in 1912. Komodo is increasingly famous globally after Douglas Burden's expedition in 1926. Komodo is described as an exotic wildness and imagination of prehistoric. This made the explorer and collector hunt Komodo dragons to serve as the museum's collection and the inhabitants of the zoo in the Indies, Europe, and America. Komodo dragons remain a target for hunting, even after the Dutch East Indies Government enacted regulations on protecting Komodo dragons in 1931.